Repositioning Microtubule Stabilizing Drugs for Brain Disorders - Varidaki, Artemis; Hong, Ye; Coffey, Eleanor T. (Frontiers in Cellular Neuroscience, 2018)
Microtubule stabilizing agents are among the most clinically useful chemotherapeutic drugs. Mostly, they act to stabilize microtubules and inhibit cell division. While not without side effects, new generations of these compounds display improved pharmacokinetic properties and brain penetrance. Neurological disorders are intrinsically associated with microtubule defects, and efforts to reposition microtubule-targeting chemotherapeutic agents for treatment of neurodegenerative and psychiatric illnesses are underway. Here we catalogue microtubule regulators that are associated with Alzheimer’s and Parkinson’s disease, amyotrophic lateral sclerosis, schizophrenia and mood disorders. We outline the classes of microtubule stabilizing agents used for cancer treatment, their brain penetrance properties and neuropathy side effects, and describe efforts to apply these agents for treatment of brain disorders. Finally, we summarize the current state of clinical trials for microtubule stabilizing agents under evaluation for central nervous system disorders.